Negative-pressure wound therapy versus standard dressings for adults with an open lower limb fracture: the WOLLF RCT - Costa, M; Achten, J; Bruce, J; Davis, S; Hennings, S; Willett, K; Petrou, S; Jeffery, S; Griffin, D; Parker, B; Masters, J; Lamb, S; et al. (NIHR Journals Library, 2018)
BACKGROUND: Open fractures of the lower limb occur when a broken bone penetrates the skin and is exposed to the outside environment. These are life-changing injuries. The risk of deep infection may be as high as 27%. The type of dressing applied after surgical debridement could potentially reduce the risk of infection in the open-fracture wound. OBJECTIVES:To assess the disability, rate of deep infection, quality of life and resource use in patients with severe open fracture of the lower limb treated with negative-pressure wound therapy (NPWT) versus standard wound management after the first surgical debridement of the wound. DESIGN:A pragmatic, multicentre randomised controlled trial. SETTING: Twenty-four specialist trauma hospitals in the UK Major Trauma Network. PARTICIPANTS:A total of 460 patients aged ≥ 16 years with a severe open fracture of the lower limb were recruited from July 2012 through to December 2015. Patients were excluded if they presented more than 72 hours after their injury or were unable to complete questionnaires. INTERVENTIONS: Negative-pressure wound therapy (n = 226) where an 'open-cell' solid foam or gauze was placed over the surface of the wound and connected to a suction pump which created a partial vacuum over the dressing versus standard dressings not involving negative pressure (n = 234). MAIN OUTCOME MEASURES: Disability Rating Index (DRI) - a score of 0 (no disability) to 100 (completely disabled) at 12 months was the primary outcome measure, with a minimal clinically important difference of 8 points. The secondary outcomes were deep infection, quality of life and resource use collected at 3, 6, 9 and 12 months post randomisaton. RESULTS:There was no evidence of a difference in the patients' DRI at 12 months. The mean DRI in the NPWT group was 45.5 points [standard deviation (SD) 28.0 points] versus 42.4 points (SD 24.2 points) in the standard dressing group, giving a difference of -3.9 points (95% confidence interval -8.9 to 1.2 points) in favour of standard dressings (p = 0.132). There was no difference in HRQoL and no difference in the number of surgical site infections or other complications at any point in the 12 months after surgery. NPWT did not reduce the cost of treatment and it was associated with a low probability of cost-effectiveness. LIMITATIONS:Owing to the emergency nature of the interventions, we anticipated that some patients who were randomised into the trial would subsequently be unable or unwilling to take part. Such post-randomisation withdrawal of patients could have posed a risk to the external validity of the trial. However, the great majority of these patients (85%) were found to be ineligible after randomisation. Therefore, we can be confident that the patients who took part were representative of the population with severe open fractures of the lower limb. CONCLUSIONS:Contrary to the existing literature and current clinical guidelines, NPWT dressings do not provide a clinical or an economic benefit for patients with an open fracture of the lower limb. FUTURE WORK:Future work should investigate alternative strategies to reduce the incidence of infection and improve outcomes for patients with an open fracture of the lower limb. Two specific areas of potentially great benefit are (1) the use of topical antibiotic preparations in the open-fracture wound and (2) the role of orthopaedic implants with antimicrobial coatings when fixing the associated fracture. TRIAL REGISTRATION:Current Controlled Trials ISRCTN33756652 and UKCRN Portfolio ID 11783. FUNDING:This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 22, No. 73. See the NIHR Journals Library website for further project information.